STANDAR KESEHATAN DAN KESELAMATAN KERJA YANG TINGGI DALAM DUNIA PELAYARAN PENDUKUNG PENGEBORAN MINYAK DAN GAS BUMI (TIPE KAPAL AHTS) - Afriandi,, Suhendra (LPPM Akper Kebonjati, 2025)
Occupational safety and health (OHS) is a crucial aspect in the shipping industry supporting oil and gas drilling, especially for Anchor Handling Tug Supply (AHTS) vessels. AHTS vessels operate in extreme sea conditions and have a high risk of occupational accidents. This research aims to analyse the applicable OHS standards, identify key challenges in the implementation of these standards, and recommend measures to improve occupational safety and health on AHTS vessels. Using a qualitative and quantitative method approach, the research involved literature study, observation, and interviews with crew members and maritime OHS experts. The results show that despite the implementation of international OHS standards such as ISM Code and SOLAS, there are still various obstacles in the field, such as lack of training, limited safety equipment, and extreme weather factors. Recommendations for regulation and supervision of OHS standard compliance on AHTS vessels.